Calcitonin pump improves nerve regeneration after transection injury and repair. Issue 2 (19th November 2014) - Yan, Ji‐Geng; Logiudice, John; Davis, John; Zhang, Lin‐Ling; Agresti, Michael; Sanger, James; Matloub, Hani S.; Havlik, Robert
ABSTRACT Introduction: After nerve injury, excessive calcium impedes nerve regeneration. We previously showed that calcitonin improved nerve regeneration in crush injury. We aimed to validate the direct effect of calcitonin on transected and repaired nerve. Methods: Two rat groups (n = 8) underwent sciatic nerve transection followed by direct repair. In the calcitonin group, a calcitonin‐filled mini‐osmotic pump was implanted subcutaneously, with a catheter parallel to the repaired nerve. The control group underwent repair only, without a pump. Evaluation and comparison between the groups included: (1) compound muscle action potential recording of the extensor digitorum longus (EDL) muscle; (2) tetanic muscle force test of EDL; (3) nerve calcium concentration; and (4) nerve fiber count and calcified spot count. Results: The calcitonin pump group showed superior recovery. Conclusions: Calcitonin affects injured and repaired peripheral nerve directly. The calcitonin‐filled mini‐osmotic pump improved nerve functional recovery by accelerating calcium absorption from the repaired nerve. This finding has potential clinical applications. Muscle Nerve 51: 229–234, 2015